Merdeka Belajar Activity Unit at Madrasah Aliyah: Program Evaluation Study Using CIPP Method - Jannatul Wardiyah; Yusnaili Budianti; Muhammad Al Farabi; Akhmad Sirojuddin; M. Alfin Fatikh (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
Evaluation is an activity to find out the teaching and learning process has achieved the goals that have been set. Meanwhile, the Independent Learning Activity Unit program is a small unit of lessons arranged sequentially from easy to difficult with respect to knowledge and skills. This study aims to determine the existence of the Independent Learning Activity Unit program in terms of context, input, process and product at MAN 3 Medan. This research is a quantitative research with CIPP model evaluation. Data was collected by means of questionnaires or questionnaires, interviews and documentation. The population is 329 students with a sample of 82 students consisting of class XI at MAN 3 Medan. Data analysis techniques with editing, tabulating, analyzing and concluding. The results showed that the Independent Learning Activity Unit program at MAN 3 Medan was effective as seen from the results of the average value of the process in the category 51.02. When viewed from the results of the context, input and product, the Independent Learning Activity Unit has complied with the guidelines and is equipped with supporting facilities.